Massive Duodenal Bleeding after the Migration of Endovascular Coils into the Small Bowel - Chung-Jo Choi; Hyun Lim; Dong-Suk Kim; Yong-Seol Jeong; Sang-Young Park; Jeong-Eun Kim (Korean Society of Gastrointestinal Endoscopy, 2019)
Among gastrointestinal emergencies, acute upper gastrointestinal bleeding remains a challenging clinical problem owing to significant patient morbidity and costs involved in management. Endoscopic hemostatic therapy is the mainstay of treatment and decreases the incidence of re-bleeding, the need for surgery, morbidity, and mortality. However, in 8%-15% of patients with upper gastrointestinal bleeding, endoscopic hemostatic therapy does not successfully control bleeding. Trans-arterial coil embolization is an effective alternative treatment for endoscopic hemostatic failure; however, this procedure can induce adverse outcomes, such as non-target vessel occlusion, vessel dissection and perforation, and coil migration. Coil migration is rare but causes severe complications, such as re-bleeding and bowel ischemia. However, in most cases, coil migration is local and involves spontaneous healing without serious complications. Here, we report the case of a patient who underwent trans-arterial coil embolization of the gastroduodenal artery with the purpose of controlling massive duodenal bleeding, resulting in a fatal outcome caused by coil migration.